Effect of contact viscosity and roughness on interface stiffness and wave propagation - Marangos, Orestes; Misra, Anil S. (My University, 2009)
The authors have developed a micromechanical methodology for modeling contact behavior of rough solids. This methodology has been applied to determine complex- valued effective normal and shear stiffnesses of interfaces by considering surface roughness, and viscous asperity contact force laws. In this work, the micromechanically derived complex effective stiffnesses are used in conjunction with the imperfectly bonded interface model to perform a parametric study by varying surface roughness, contact viscosities, and frequency of the incident wave. We find that the surface roughness and asperity properties compete in determining the stiffness behavior, and consequently, the wave propagation behavior of rough interfaces. © 2009 American Institute of Physics.
Keywords: Acoustics; Effective stiffness; Interfaces; Reflection; Transmission